Women, Islam and familial intimacy in colonial South Asia - Alam, Asiya (New Delhi : Manohar, 2025)
Women, Islam and Familial Intimacy in Colonial South Asia highlights the rich tradition of protest and defiance among the Muslim women of colonial India. Bringing together a range of archival material including novels, pamphlets, commentaries and journalistic essays, it narrates a history of Muslim feminism conversing with, and confronting the dominant and influential narratives of didactic social reform. The book reveals how discussion about marriage and family evoked claims of women$1 (Bs freedom and rights in a highly charged literary and cultural landscape where lesser-known female intellectuals jostled for public space alongside well-known male social reformers. Definitions of Islamic ethics remained central to these debates, and the book illustrates how claims of social obligation, religious duty and freedom balanced and negotiated each other in a period of nationalism and reform. By doing so, it also illuminates a story of Muslim politics that goes beyond the well-established accounts of Muslim separatism and the Pakistan movement.s
Keywords: Feminism--History-- 20th century-- South Asia; Marriage--History--19th century--South Asia--20th century; Muslim women--Social conditions--19th century--South Asia--20th century